Comment on Arm's-Length Intimacy: Employment As Relationship - Scott Baker (Washington University Journal of Law & Policy, 2011)
The author discusses the article “Arm's-Length Intimacy: Employment as Relationship,” by Marion Crain. The author states that Crain's article is provocative for it forces the reader to identify ways in which family and work differs. He says that the article has weaknesses which limit its broader applicability and rest on the assumptions of how labor markets work. Furthermore, he mentions Crain's assumption that employers have the bargaining power and employees are powerless in the relationship.
Keywords: Industrial relations; Employment at will; Liability for emotional distress; Domestic relations; Law & economics; Collective bargaining; Employment terminations; Work and family